Rainbow warrior : my life in color - Baker, Gilbert, 1951-2017 (Chicago Review Press, 2019)
"The never-published memoir of the visual artist and social justice activist who created the Rainbow Flag, which became an international emblem of the modern LGBTQ+ movement"--